MAKNA GERAK TARI JEPIN SUSON SIREH DI DESA SAWAH TUNJUK KECAMATAN SAYAN KABUPATEN MELAWI KALIMANTAN BARAT - Rizqyanti Ayu Lestari; Imma Fretisari; Ismunadar Ismunadar (Universitas Tanjungpura, 2019)
Abstrack The background of this research is that there is a uniqueness of the variety of movements of Jepin Suson sireh dance in which the various movements have their own meaning associated with everyday life. Specifically the problem in this research is how the movements of Jepin Suson Sireh Dance in Sawah Tunjuk Village, Sayan District, Melawi District, West Kalimantan, and how the design of the implementation of Jepin Suson Sireh Dance in Sawah Tunjuk Village, Sayan District, Melawi District, West Kalimantan. The method used in this study is descriptive method with qualitative research. The approach used is a semiotic approach which is a science in the form of signs. The data sources in this study were Mr. Amri, Mr. Suhendra, Mr. Rajab and Mr. Eka Candra. The data in this study are the results of observations, interview guidelines and documentation tools. The technique of testing the validity of the data in the form of extension and analysis after data collection. The results of this study are in the meaning of movement of the Suson Sireh dance in Sawah Tunjuk Village, Sayan District, Melawi District, West Kalimantan, a meeting with resource persons who knew the variety of dance movements of the Suson Sireh. Susilo Sireh's Jepin dance has 9 steps, in the dance movement, each of which has meaning. Keywords: meaning of motion, jepin suosn sireh dance.